Motivations of Non-Muslim Customers Using Islamic Banking Services in Indonesia with Phenomenological Study - Moh. Kusnimad Sofi Ari; M. Aldi Ainul Rohim (Jurnal Ekonomi islam and Manajemen, 2025)
This phenomenological study explores the motivations of non-Muslim customers using Islamic banking services in Indonesia. Despite Islamic banks traditionally serving Muslim communities, the growing number of non-Muslim customers reflects a significant shift in market dynamics. Through in-depth interviews and qualitative analysis, this research uncovers key factors that drive non-Muslims to engage with Islamic banks. These motivations include perceptions of ethical and transparent financial practices, trust in product quality, competitive service offerings, and favorable banking costs. Additionally, the emphasis on risk-sharing principles and avoidance of interest resonates with broader ethical financial preferences, even beyond religious affiliations. Accessibility and location convenience also influence customer choices, alongside positive reputations supported by effective promotions. Importantly, psychological factors such as satisfaction and perceived benefits reinforce continued patronage among non-Muslims. Socio-cultural acceptance, especially in Muslim minority regions, facilitates openness toward Islamic banking. This study highlights that non-Muslim customers are motivated not solely by religious considerations but also by practical, economic, and ethical reasons. The findings suggest that Islamic banks in Indonesia can expand their market by addressing diverse customer needs while maintaining Shariah-compliant services. Understanding these motivations helps stakeholders design inclusive strategies that foster wider acceptance and trust. Overall, the study contributes valuable insights into the cross-cultural appeal of Islamic banking in Indonesia’s pluralistic society and underscores the importance of customer-centric approaches for sustainable growth.